PELATIHAN KONSELING TEMAN SEBAYA (Peer counseling Training) PADA ANGGOTA PIK-R DI MTsS THAWALIB - Abdullah Muhhammad Abrar; Mai Murni; Andrea Prima Yoga (Universitas Negeri Padang, 2023)
This study aims to provide peer counseling training to PIK-R members for students at MTsS Thawalib Padang. The method used in this study was carried out through interviews with counseling teachers, conducting FGDs with students in groups, as well as conducting interventions in the form of training for students and PIK-R members. The series of activities was attended by 70 students consisting of 39 boys and 31 girls. The results of the intervention activities that have been carried out are that students are able to do peer counseling well and can understand how to do peer counseling well.